Dīwān-i Khāzin - al-Khāzin, ʿAbdallāh b. Aḥmad (Miras Maktoob, ISBN: 9789004365452., 2019)
About fifty years ago, during renovation works in the complex of Imam Reza in Mashhad, a hoard of manuscripts was discovered in a secret niche. These manuscripts had probably been stashed away in a time of unrest to prevent them from getting looted or destroyed. Among them, there was one quite remarkable codex, copied in 481/1088 and published here, containing the divan of ʿAbdallāh b. Aḥmad al-Khāzin, a poet who belonged to entourage of the Buyid vizier Ṣāḥib b. al-ʿAbbād (d. 385/995). Al-Khāzin was his librarian for a time, until he was banished from the court. Since most of the poems are dedicated to Fakhr al-Dawla (d. 387/997) and Ibn al-ʿAbbād, they must have been written after Fakhr al-Dawla was brought to power by Ibn al-ʿAbbād in 373/983. Even with sections missing, this manuscript contains no less than 1.922 verses by al-Khāzin, much more than the 241 verses quoted in al-Thaʿālibī's (d. 429/1038) Yatīmat al-dahr.